The Harmony Level Among Lecturers of The Teacher Education Institute in Peninsular Malaysia - Kartini Abdul Mutalib; Mazlan Aris; Masitah Mohammad Yusof; Ahamad Rahim; Suhaili Mohd Yusoff (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
Harmony and enjoyment at workplace have a positive influence on commitment, work productivity and loyalty to the organization. Therefore, this study aims to identify the level of harmony that consists of the dimensions of self-motivation, external motivation, physical environment, psychosocial and personal health among IPG Campus lecturers in Penninsular Malaysia. This study also aims to identify the differences level of harmony based on demographic factors (gender, age, academic qualifications and service duration) among the lecturers. Data was collected by a cross-sectional survey through the Teacher Institution's Well-being Questionnaire (TIWEQ) constructed by the researchers. The questionnaire had also been tested for the validity and reliability. A total of 857 samples were involved in this study. The findings of the study showed that the level of harmony among IPG campus lecturers in Peninsular Malaysia is at a high level of 53.2 percent (n = 456). Based on the dimensions, it was found that the highest mean value is the self-motivation dimension (M = 3.68, SD = 0.38) while the lowest mean value is the personal health dimension (M = 2.79, SD = 0.59). This finding contributes to the field of knowledge that the importance of balance between external and internal harmony for the sustainability of the education system. In addition, it is also necessary to create a harmony profile for each IPG.